Francuszczyzna w rejestrze środków publicystycznych (na przykładzie felietonów Ludwika Stommy) - v Śliwińska (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2019)
The present paper focuses on gallicisms (French loanwords) which appear in Ludwik Stomma’s feature articles published in Polityka between 2005 and 2007. In order to analyze aspects of French loanwords in journalistic idiom, it is necessary to start by drawing up the guidelines for the description of empirical data excerpted from the given text type. The author has chosen structural-functional, semantic, and quantitative analyses of gallicisms. The first part of the research leads to the division of linguistic material into: quotes, proper nouns, and lexical borrowings. The semantic criteria used to introduce the distinctions between the gallicisms made it possible to propose lexico-semantic categories and numerous subcategories. The frequency of autosemantic word forms allowed to create a list of key terms of highest textual frequency and to present the types of syntactic accommodation of the most frequent elements. The dominant properties established during the course of structural, semantic, and quantitative analyses can be regarded as typical of Ludwik Stomma’s idiolect.